Iodinated Contrast Prior to Thrombolysis Was Not Associated With Worse Intracranial Hemorrhage. (2nd March 2015) - Radecki, Ryan P.; Azam, Arif; Doshi, Pratik B.; Banuelos, Rosa C.; Panagos, Peter
Abstract Objectives The objective was to assess relative incidence of clinical adverse effects between patients receiving, and not receiving, iodinated contrast prior to thrombolysis. Methods This was a retrospective registry review of patients presenting to the emergency department treated with recombinant tissue‐type plasminogen activator (rt‐PA) for acute ischemic stroke between 2004 and 2012. The authors compared the occurrence of all grades of intracranial hemorrhage (ICH), symptomatic intracranial hemorrhage (sICH), and in‐hospital deaths between patients undergoing computed tomographic angiography (CTA) prior to thrombolysis and those who did not. Results A total of 1, 014 patients were available for analysis meeting inclusion criteria. A total of 473 patients underwent CTA prior to rt‐PA administration. Baseline characteristics were generally similar across groups, excepting fewer signs of acute infarct and old stroke in the CTA group (28.8% vs. 8.5% and 9.9% vs. 3.7%, respectively) and creatinine. Adverse event outcomes were not consistently distributed across the groups. Patients in the CTA group had a similar incidence of any ICH (11.0% vs. 8.1%, p = 0.120), but fewer type II parenchymal hemorrhages (2.1% vs. 4.6%, p = 0.025) and fewer in‐hospital deaths (7.2% vs. 12.6%, p = 0.005). Conclusions No consistent harms were observed in association with intravenous iodinated contrast prior to rt‐PA administration. It is reasonable to continue CTA prior to thrombolysis as clinically indicated.